2007
DOI: 10.1182/blood-2007-01-065573
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodide imaging and radiovirotherapy of multiple myeloma using VSV(Δ51)-NIS, an attenuated vesicular stomatitis virus encoding the sodium iodide symporter gene

Abstract: Multiple myeloma is a radiosensitive malignancy that is currently incurable. Here, we generated a novel recombinant vesicular stomatitis virus [VSV(⌬51) - IntroductionMultiple myeloma is a malignancy of antibody-secreting plasma cells that reside predominantly in bone and bone marrow and secrete a monoclonal immunoglobulin. 1 The disease responds initially to alkylating agents, corticosteroids, and thalidomide, but eventually becomes refractory. 2 Multiple myeloma remains incurable causing more than 10 000 dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 52 publications
3
117
0
1
Order By: Relevance
“…The study reported here is of particular interest in the recent and highly promising field of NIS-based gene therapy for non-thyroidal cancers (Chung 2002), especially when NIS is used in synergy with other genes such as canstatin (an angiogenic inhibitor; Magnon et al 2007) or with virotherapy (Dingli et al 2004, Goel et al 2007). The targeted transduction and the expression of NIS in cancer cells can allow tumor cell destruction by radioiodine treatment as well as in vivo imaging for the generation and investigation of safe and efficient gene delivery systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported here is of particular interest in the recent and highly promising field of NIS-based gene therapy for non-thyroidal cancers (Chung 2002), especially when NIS is used in synergy with other genes such as canstatin (an angiogenic inhibitor; Magnon et al 2007) or with virotherapy (Dingli et al 2004, Goel et al 2007). The targeted transduction and the expression of NIS in cancer cells can allow tumor cell destruction by radioiodine treatment as well as in vivo imaging for the generation and investigation of safe and efficient gene delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, important therapeutic effects can be achieved without uniform systemic gene delivery into all tumor cells. However, despite the highly promising results obtained recently (Goel et al 2007, Magnon et al 2007, it is still critical to develop better gene delivery systems and to improve the iodide uptake capacity of targeted cells in order to lower the administered radiation doses. As with our experiments, the above-mentioned gene therapy approach is based on the transient expression of NIS in target cells.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the oncolytic potency of VSV, investigators have genetically modified the virus to express a variety of transgenes such as chemokine-binding protein, IL-12, and fusogenic glycoproteins (Ebert et al, 2004;Shin et al, 2007;Wu et al, 2008). In addition, Goel and colleagues have demonstrated that addition of the human thyroidal sodium iodide symporter gene to the VSV genome permits radioiodine imaging of the sites of viral infection as well as enhancement of the antitumor activity of VSV by using 131 I, a b particle-emitting radionuclide (Goel et al, 2007). Although there has been intensive preclinical work developing VSV for cancer therapy, clinical translation of VSV has lagged behind, mainly because of concerns about the neurovirulence of VSV when administered to animals (Clarke et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…13,15 A similar strategy was employed with VSV expressing the human sodium iodine symporter that resulted in the accumulation of radioactive iodine at the tumor site. 16 Both of these recombinant VSV strategies were shown to delay tumor growth in murine models; however, their action is restricted to cells that are directly infected by VSV.…”
Section: Introductionmentioning
confidence: 99%